Coextruded multilayer film, laminate, and packaging bag

By using coextruded multilayer film as the laminated material, the problem of insufficient heat sealing of the packaging bag in the bag making process is solved, high circulation regeneration and excellent heat sealing are achieved, and the mechanical strength and production efficiency of the packaging bag are improved.

CN119866270APending Publication Date: 2025-04-22TOPPAN HOLDINGS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380065561.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-02
Filing Date
2023-10-31
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the bag making process, existing packaging bags have problems such as insufficient heat sealing, narrow temperature and poor productivity, and insufficient strength of packaging bags. Especially when using laminates, the substrate layer is prone to heat adhere to the fixture or wrinkles.

Method used

A coextruded multilayer film is used, which has a surface layer and a back layer, which contains a polyethylene resin, and the surface layer contains a resin with a melting point higher than the polyethylene resin, and the thickness of the surface layer is 0.3 μm or more and 6 μm or less. When such a multilayer film is used as a material for a laminate, it is possible to improve the recycle and heat sealing properties of the laminate and simplify the manufacturing process by coextrusion.

Benefits of technology

High circulation reproducibility and excellent heat sealing properties of the laminated body are achieved, the mechanical strength and production efficiency of the packaging bag are improved, and the adverse conditions of the substrate layer in the heat sealing process are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866270A_ABST
    Figure CN119866270A_ABST
Patent Text Reader

Abstract

The coextruded multilayer film according to one aspect of the present disclosure is a coextruded multilayer film having a first layer and a second layer, in which the second layer contains a polyethylene resin, the first layer contains a resin having a higher melting point than the polyethylene resin, and the thickness of the first layer is 0.3 [mu] m or more and 6 [mu] m or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to coextruded multilayer films, laminates, and packaging bags. Background Art

[0002] Packaging bags use a combination of various materials depending on the nature of the contents to be packaged, the amount of the contents, post-processing to prevent the contents from deteriorating, the method of transporting the packaging bag, the method of opening the packaging bag, the method of disposal, etc.

[0003] For example, in the case of packaging bags using flexible packaging laminated films, the following two methods are used in combination: biaxially stretched films such as polypropylene resin or polyester resin are used to obtain mechanical strength of the packaging bag; polyethylene resin, polypropylene resin, ethylene-vinyl acetate copolymer, etc. are used as heat-sealing materials to seal the contents in the packaging bag. In addition, aluminum foil or ethylene-vinyl alcohol copolymer is laminated to suppress deterioration of the contents.

[0004] The laminates using the above-mentioned functionally separated various raw materials are designed with the focus on adaptability to various processes from packaging of the contents to transportation, storage, and unsealing. However, due to the increased awareness of environmental issues in recent years, the focus has begun to be placed on the functions of resource conservation and recyclability of various products, and the same functions have begun to be required for the laminates used in packaging bags. It is generally believed that when the proportion of the main resin contained in the packaging material is 90% by mass or more, the recyclability is high, but most of the existing packaging materials are composed of multiple resin materials or, depending on the situation, paper and metal materials, and because they do not meet the above standards, they cannot be recycled. This is the current situation.

[0005] Therefore, Patent Document 1 describes that in a laminate having a substrate, an adhesive layer, and a heat seal layer, the substrate and the heat seal layer are formed of polyethylene resin. By forming the substrate and the heat seal layer with the same material, the above-mentioned recyclability standard can be easily achieved.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-55157 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] However, when the laminate described in Patent Document 1 is used in a packaging bag, the bag-making process of forming the packaging bag includes the following steps: the heat-sealing layers (sealant layers) of the laminate are facing each other, and pressure is applied from the outside of the substrate layer of the laminate using a high-temperature clamp to clamp it, so that it is thermally melted and bonded (heat-sealed). The clamp of the heat sealer becomes hot, and the outside of the substrate layer directly contacting the clamp is exposed to high temperature. Therefore, for the conventional laminate, the substrate layer is heated and adheres to the clamp or wrinkles are generated in the heat-sealed part, and the heat-sealing property is insufficient. Therefore, sometimes the narrow suitable conditions for bag-making temperature, poor productivity, and insufficient strength of the packaging bag become technical problems.

[0011] Therefore, the present disclosure provides a laminate having excellent recyclability and excellent heat-sealing properties and a packaging bag using the laminate. In addition, the present disclosure provides a coextruded multilayer film having excellent recyclability and excellent heat-sealing properties when used as a material for a laminate.

[0012] Means for solving technical problems

[0013] One aspect of the present disclosure relates to a coextruded multilayer film, which is a coextruded multilayer film having a surface layer and a back layer, wherein the back layer comprises a polyethylene resin, the surface layer comprises a resin having a melting point higher than that of the polyethylene resin, and the thickness of the surface layer is 0.3 μm or more and 6 μm or less. When this coextruded multilayer film is used as a material for a laminate, the resulting laminate has excellent recyclability and excellent heat sealability. In addition, this coextruded multilayer film has excellent manufacturing efficiency because it can be manufactured in one process using a coextrusion method.

[0014] One aspect of the present disclosure relates to a coextruded multilayer film, which is a coextruded multilayer film having a surface layer, an intermediate layer, and a back layer, wherein the intermediate layer comprises a polyethylene resin, the surface layer and the back layer comprise a resin having a melting point higher than that of the polyethylene resin, and the thickness of the surface layer is 0.3 μm or more and 6 μm or less. This coextruded multilayer film is difficult to curl, and when used as a material for a laminate, the resulting laminate has excellent recyclability and heat sealability. In addition, this coextruded multilayer film has excellent manufacturing efficiency because it can be manufactured in one process using a coextrusion method.

[0015] Another aspect of the present disclosure relates to a laminate, which is a laminate having the above-mentioned coextruded multilayer film, a first adhesive layer provided on the back layer side of the coextruded multilayer film, and a sealant layer in sequence, wherein the sealant layer contains a polyethylene resin, and the content of the polyethylene resin in the laminate is 90% by mass or more based on the total amount of the laminate. Such a laminate has excellent recyclability and excellent heat sealing properties.

[0016] In one embodiment, the difference between the heat seal start temperature of the surface layer of the coextruded multilayer film and the heat seal start temperature of the sealant layer may be 40° C. or more. In one embodiment, the laminate may further include a polyethylene film and a second adhesive layer between the first adhesive layer and the sealant layer from the first adhesive layer side. In one embodiment, the absolute value of the molecular orientation degree of the polyethylene film may be less than 1.07.

[0017] In one embodiment, the polyethylene film may include a surface layer, an intermediate layer, and a back layer in sequence. In the polyethylene film, the probe drop temperature of the intermediate layer is higher than the probe drop temperature of the surface layer and is higher than the probe drop temperature of the back layer. The surface layer of the polyethylene film includes a 0.926 g / cm 3 Polyethylene resin with a density above .

[0018] In one embodiment, the laminate may further include a gas barrier layer between the coextruded multilayer film and the polyethylene film. In one embodiment, the laminate may further include a gas barrier layer between the polyethylene film and the sealant layer.

[0019] Another aspect of the present disclosure relates to a packaging bag formed using the above-mentioned laminate, which has excellent recyclability and heat-sealing properties.

[0020] Effects of the Invention

[0021] According to the present disclosure, a laminate having excellent recyclability and excellent heat sealability and a packaging bag using the laminate can be provided. In addition, according to the present disclosure, a coextruded multilayer film having excellent recyclability and excellent heat sealability when used as a material for a laminate can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic cross-sectional view of a coextruded multilayer film according to one embodiment of the present disclosure.

[0023] Figure 2 It is a schematic cross-sectional view of a coextruded multilayer film according to one embodiment of the present disclosure.

[0024] Figure 3 It is a schematic cross-sectional view of a stacked body according to one embodiment of the present disclosure.

[0025] Figure 4 It is a schematic cross-sectional view of a stacked body according to one embodiment of the present disclosure.

[0026] Figure 5 It is a schematic cross-sectional view of a stacked body according to one embodiment of the present disclosure.

[0027] Figure 6 It is a schematic cross-sectional view of a coextruded multilayer film according to one embodiment of the present disclosure.

[0028] Figure 7 It is a schematic cross-sectional view of a stacked body according to one embodiment of the present disclosure.

[0029] Figure 8 It is a schematic cross-sectional view of a stacked body according to one embodiment of the present disclosure.

[0030] Fig. 9 It is a schematic cross-sectional view of a stacked body according to one embodiment of the present disclosure. DETAILED DESCRIPTION

[0031] The following is based on the situation while referring to the attached Figure 1 The embodiments of the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments.

[0032] [Coextruded multilayer film of the first aspect]

[0033] The coextruded multi-layer film according to the first aspect of the present disclosure is described below.

[0034] <First embodiment>

[0035] Figure 1 It is a schematic cross-sectional view of a coextruded multilayer film according to the first embodiment of the present disclosure. Figure 1 The coextruded multilayer film 1 shown has a surface layer (first layer) 10 and a back layer (second layer) 11. The coextruded multilayer film 1 is produced by a coextrusion method. The thickness of the surface layer 10 is 0.3 μm or more and 6 μm or less. Each layer is described below.

[0036] (surface layer)

[0037] The surface layer 10 contains a resin having a higher melting point than the polyethylene resin contained in the back layer 11. The surface layer 10 is provided to prevent the bad situation when heat sealing is performed during bag making or filling and sealing, and to ensure the heat sealing suitability. Based on this function, the surface layer 10 can be provided as the outermost layer of the laminate described later.

[0038] Examples of the resin having a higher melting point than the polyethylene resin include polypropylene resin, polyester resin, polyamide resin, ethylene-vinyl alcohol copolymer, polyvinyl alcohol resin, polyvinylidene chloride resin, and polystyrene resin. These resins may be used alone or in combination of two or more.

[0039] The melting point of the resin having a higher melting point than the polyethylene resin may be 160° C. or higher, 180° C. or higher, or 200° C. or higher from the viewpoint that the coextruded multilayer film 1 has more excellent heat sealability.

[0040] The content of the resin having a melting point higher than that of the polyethylene resin may be 10 mass % or more, 30 mass % or more, 50 mass % or more, 70 mass % or more, 90 mass % or more, 95 mass % or more, or 100 mass % based on the total amount of the surface layer 10 .

[0041] When the coextruded multilayer film 1 is produced by the T-die method, the melt flow rate (MFR) of the resin having a melting point higher than that of the polyethylene resin is preferably 3 g / 10 minutes or more and 20 g / 10 minutes or less. By making the MFR 3 g / 10 minutes or more, the processing suitability of the coextruded multilayer film 1 can be improved. In addition, by making the MFR 20 g / 10 minutes or less, the coextruded multilayer film 1 produced can be prevented from breaking.

[0042] When the coextruded multilayer film 1 is produced by the inflation method, the MFR of the resin having a melting point higher than that of the polyethylene resin is preferably 0.1 g / 10 minutes or more and 5 g / 10 minutes or less. By making the MFR 0.1 g / 10 minutes or more, the processing suitability of the coextruded multilayer film 1 can be improved. In addition, by making the MFR 5 g / 10 minutes or less, the film forming property can be improved.

[0043] The surface layer 10 may further include a polyethylene resin. When the surface layer 10 includes a polyethylene resin, even if an adhesive resin is not used between the layers, a bonding strength that makes it difficult for the layers to peel off can be imparted when the surface layer 10 and the layer formed by the polyethylene resin are attached. The content ratio of the polyethylene resin can be 10% by mass or more, 30% by mass or more, 50% by mass or more, 70% by mass or more, or 90% by mass or more based on the total amount of the surface layer 10.

[0044] The thickness of the surface layer 10 is 0.3 μm or more and 6 μm or less. When the thickness of the surface layer 10 is 0.3 μm or more, the heat sealability of the coextruded multilayer film 1 becomes excellent. In addition, when the thickness of the surface layer 10 is 6 μm or less, the recyclability of the coextruded multilayer film 1 becomes excellent. The thickness of the surface layer 10 may be 0.5 μm or more or 1 μm or more, and may be 5 μm or less or 3 μm or less.

[0045] (Back layer)

[0046] The back layer contains polyethylene resin. Examples of such polyethylene resin include ultra-low density polyethylene resin (abbreviated as VLDPE, density: less than 0.910 g / cm 3 ), low-density polyethylene resin (abbreviation: LDPE, density: 0.910g / cm 3 Above and less than 0.930g / cm 3 ), medium density polyethylene resin (abbreviation: MDPE, density: 0.930g / cm 3 Above and less than 0.942g / cm 3), linear low-density polyethylene resin (abbreviation: LLDPE, density: 0.930g / cm 3 Above and less than 0.942g / cm 3 ) and high-density polyethylene resin (abbreviation: HDPE, density: 0.942g / cm 3 above).

[0047] The content of the polyethylene resin may be 10% by mass or more, 30% by mass or more, 50% by mass or more, 70% by mass or more, 90% by mass or more, 95% by mass or more, or 100% by mass based on the total amount of the back layer.

[0048] The thickness of the coextruded multilayer film 1 is not particularly limited, and can be appropriately changed according to price or purpose in consideration of suitability as a packaging material or lamination suitability of other layers. The thickness of the coextruded multilayer film 1 is preferably 10 μm or more and 50 μm or less, more preferably 15 μm or more and 40 μm or less. When the thickness of the coextruded multilayer film is greater than 15 μm, there is a tendency to fully ensure stability in manufacturing. When the thickness of the coextruded multilayer film is greater than 40 μm, there is a tendency to suppress manufacturing costs.

[0049] The content ratio of the polyethylene resin in the coextruded multilayer film 1 may be 70% by mass or more, 80% by mass or more, or 90% by mass or more based on the total amount of the coextruded multilayer film 1 .

[0050] The coextruded multilayer film 1 can be produced by forming the materials constituting each layer into a film using a coextrusion method such as a T-die method or an inflation method. The coextruded multilayer film 1 may be unstretched or may be subjected to a stretching treatment.

[0051] Various additives may be added to each layer of the coextruded multilayer film 1. Examples of such additives include flame retardants, lubricants, anti-blocking agents, antioxidants, light stabilizers, and tackifiers.

[0052] The surface of the coextruded multilayer film 1 may be subjected to an adhesion-facilitating treatment by dry surface treatment such as corona treatment or atmospheric pressure plasma treatment.

[0053] <Second embodiment>

[0054] A coextruded multilayer film according to a second embodiment will be described below. Aspects not described below are the same as those of the coextruded multilayer film according to the first embodiment unless there is any mismatch. Figure 2 It is a schematic cross-sectional view of a coextruded multi-layer film according to a second embodiment of the present disclosure. Figure 2 The coextruded multilayer film 2 shown has, in order, a surface layer 10, an intermediate layer 12, and a back layer 11. The intermediate layer will be described below.

[0055] (Middle layer)

[0056] The middle layer 12 includes a polyethylene resin. Examples of such polyethylene resins include ultra-low density polyethylene resins, low density polyethylene resins, medium density polyethylene resins, linear low density polyethylene resins, and high density polyethylene resins. In addition, the middle layer 12 may be an adhesive resin such as maleic anhydride grafted modified polyethylene. The middle layer 12 may include resins other than polyethylene resins. The middle layer 12 may be a single layer or multiple layers.

[0057] The content of the polyethylene resin based on the total amount of the intermediate layer 12 may be 10% by mass or more, 30% by mass or more, 50% by mass or more, 70% by mass or more, 90% by mass or more, 95% by mass or more, or 100% by mass.

[0058] As mentioned above, the coextruded multilayer films of the first and second embodiments have been described, but the coextruded multilayer film of the first aspect of the present disclosure is not limited to the above-described embodiments.

[0059] [Laminate of the first aspect]

[0060] The laminated body according to the first aspect of the present disclosure will be described below.

[0061] <First embodiment>

[0062] Figure 3 It is a schematic cross-sectional view of a laminated body according to the first embodiment of the present disclosure. Figure 3 The laminate 100 shown includes a coextruded multilayer film 1, a first adhesive layer 40, a polyethylene film 20, a second adhesive layer 50, and a sealant layer 30. The laminate 100 includes an inorganic oxide layer 14 and a gas barrier coating layer 15 as gas barrier layers between the polyethylene film 20 and the sealant layer 30. Each layer is described below.

[0063] (Polyethylene film)

[0064] The polyethylene film 20 serves to improve the processing stability when the inorganic oxide layer 14 is set. In addition, the polyethylene film 20 serves to suppress the deterioration of the gas barrier properties after heat sterilization. The polyethylene film 20 is a layer containing a polyethylene resin. There is no particular limitation on the polyethylene resin contained in the polyethylene film 20. From the perspective of excellent processing stability when the gas barrier layer is set and excellent heat resistance that can maintain gas barrier properties after heat sterilization, high-density polyethylene resin and medium-density polyethylene resin are preferred. These materials can be formed from substances derived from petroleum, can be formed from substances derived from plants, or can be a mixture thereof. The surface of the polyethylene film 20 can also be subjected to dry surface treatment such as corona treatment and atmospheric pressure plasma treatment to implement easy bonding treatment.

[0065] The thickness of the polyethylene film 20 is not particularly limited, and can be appropriately determined according to price or purpose in consideration of suitability as a packaging material or lamination suitability of other layers, and is preferably 5 μm to 100 μm, more preferably 10 μm to 60 μm, and further preferably 15 μm to 40 μm. When the thickness of the polyethylene film 20 is 5 μm or more, the laminate 100 tends to have better heat resistance and increased stability in manufacturing. When the thickness of the polyethylene film 20 is 100 μm or less, an increase in manufacturing cost can be suppressed.

[0066] The polyethylene film 20 can be made by using a coextrusion method such as a T-die method or an inflation method to make a polyethylene resin into a film. When the polyethylene film 20 is made using the T-die method, the melt flow rate (MFR) of the polyethylene resin is preferably more than 3g / 10 minutes and less than 20g / 10 minutes. By making the MFR more than 3g / 10 minutes, the processing suitability of the laminate can be improved. In addition, by making the MFR less than 20g / 10 minutes, the film produced can be prevented from breaking.

[0067] When the polyethylene film 20 is made by the inflation method, the MFR of the polyethylene resin is preferably 0.1 g / 10 minutes or more and 5 g / 10 minutes or less. By making the MFR 0.1 g / 10 minutes or more, the processing suitability of the laminate can be improved. In addition, by making the MFR 5 g / 10 minutes or less, the film forming property can be improved.

[0068] The content of the polyethylene resin may be 90% by mass or more, 95% by mass or more, or 100% by mass based on the total amount of the polyethylene film 20 .

[0069] The polyethylene film 20 may also include various additives such as flame retardants, lubricants, anti-caking agents, antioxidants, light stabilizers, and adhesion imparting agents. The polyethylene film 20 may also have functions such as gas barrier properties, oxygen absorption, high rigidity, and light shielding properties. Such functions may also be appropriately changed according to the purpose of the laminate 100.

[0070] The polyethylene film 20 may be unstretched or stretched. "The polyethylene film 20 is unstretched" means that the absolute value of the molecular orientation of the polyethylene film 20 is less than 1.07. When the polyethylene film 20 is unstretched (the absolute value of the molecular orientation is less than 1.07), the inorganic oxide layer 14 tends to be difficult to peel off and the adhesion with the sealant layer 30 tends to be improved. The absolute value of the molecular orientation refers to the value measured by the method described in the examples described later.

[0071] (Inorganic oxide layer)

[0072] In the laminate 100, an inorganic oxide layer 14 is formed on at least one surface of the polyethylene film 20. The inorganic oxide layer 14 imparts oxygen barrier properties and water vapor barrier properties to the laminate 100. Since the laminate 100 includes the inorganic oxide layer 14 and the gas barrier coating layer 15 between the polyethylene film 20 and the sealant layer 30, the tensile force applied to the gas barrier layer is reduced even when the laminate 100 is bent by the contents when the packaging bag is made. As a result, the packaging bag has excellent gas barrier properties.

[0073] As the composition of the inorganic oxide layer 14, for example, a vapor-deposited layer formed of a metal oxide such as aluminum oxide, silicon oxide, magnesium oxide, and tin oxide can be cited. From the viewpoint of transparency and barrier properties, the metal oxide can be selected from aluminum oxide, silicon oxide, and magnesium oxide. Furthermore, when considering the cost, it is selected from aluminum oxide and silicon oxide. Furthermore, by making the inorganic oxide layer 14 a barrier film formed of a metal oxide, a high barrier property can be obtained with an extremely thin layer within a range that does not affect the recyclability of the stack 100.

[0074] The film thickness of the vapor-deposited film formed by aluminum oxide is preferably more than 5nm and less than 30nm. When the film thickness is more than 5nm, sufficient gas barrier properties can be obtained. When the film thickness is less than 30nm, the deformation caused by the internal stress of the film can be suppressed to produce cracks, and the reduction of gas barrier properties can be suppressed. In addition, when the film thickness exceeds 30nm, the cost is easy to increase due to the increase in the amount of material used and the long film formation time, so it is not preferred from an economic point of view. From the same viewpoint as above, the film thickness of the vapor-deposited film is more preferably more than 7nm and less than 15nm.

[0075] The film thickness of the inorganic oxide layer formed by silicon oxide is preferably 5 nm or more and 100 nm or less. When the film thickness is 5 nm or more, sufficient gas barrier properties can be obtained. In addition, when the film thickness is 100 nm or less, even if an external load such as bending or stretching is applied after the inorganic oxide layer 21 is formed, cracks can be suppressed in the inorganic oxide layer 21, and the reduction in gas barrier properties can be suppressed. In addition, when the film thickness exceeds 100 nm, the cost is likely to increase due to the increase in the amount of material used and the prolonged film formation time, so it is not preferred from an economic point of view. From the same point of view as above, the film thickness of the vapor-deposited film is more preferably 10 nm or more and 50 nm or less.

[0076] The inorganic oxide layer 14 can be formed by vacuum film formation, for example. In vacuum film formation, physical vapor deposition or chemical vapor deposition can be used. Examples of physical vapor deposition include vacuum evaporation, sputtering, and ion plating, but are not limited to these. Examples of chemical vapor deposition include thermal CVD, plasma CVD, and optical CVD, but are not limited to these.

[0077] In the above-mentioned vacuum film formation, it is particularly preferred to use a resistance heating vacuum evaporation method, an EB (Electron Beam) heating vacuum evaporation method, an induction heating vacuum evaporation method, a sputtering method, a reactive sputtering method, a dual magnetron sputtering method, a plasma chemical vapor deposition method (PECVD method), etc. Among them, if productivity is considered, the vacuum evaporation method is currently the most preferred. As a heating means for the vacuum evaporation method, it is preferred to use any one of an electron beam heating method, a resistance heating method, and an induction heating method.

[0078] A primer layer may be formed on the surface of the polyethylene film 20 on which the inorganic oxide layer 14 is formed using a known primer coating liquid. The primer layer may be formed using a coating liquid containing, for example, an acrylic resin, an epoxy resin, an acrylic urethane resin, a polyester polyurethane resin, a polyether polyurethane resin, or the like. From the viewpoint of heat resistance and interlayer adhesive strength, the primer layer may be formed using a coating liquid containing an acrylic urethane resin or a polyester polyurethane resin.

[0079] The method of coating the coating liquid for forming the primer layer may be a known coating method, and examples thereof include a dipping method, a method using a sprayer, a coater, a printer, a brush, etc. In addition, as the types of coaters and printers used in these methods and their coating methods, examples thereof include gravure coaters such as direct gravure method, reverse gravure method, reverse contact gravure method, offset gravure method, etc., reverse roll coaters, micro gravure coaters, sealed blade coaters, air knife coaters, dip coaters, rod coaters, comma coaters, die coaters, etc.

[0080] The method for drying the primer layer is not particularly limited, and examples thereof include a method of utilizing natural drying, a method of drying in an oven set to a predetermined temperature, a method of using a dryer attached to a coater, such as an arch dryer, a suspension dryer, a drum dryer, an infrared dryer, etc. The drying conditions can be appropriately selected according to the drying method, and for example, in a method of drying in an oven, the primer layer can be dried at 60 to 100° C. for about 1 second to 2 minutes.

[0081] The thickness of the primer layer is preferably 0.01 μm or more, 0.03 μm or more, or 0.05 μm or more from the viewpoint of obtaining sufficient interlayer adhesion. The thickness of the primer layer is preferably 5 μm or less, 3 μm or less, or 2 μm or less from the viewpoint of excellent gas barrier properties.

[0082] (Gas barrier coating layer)

[0083] The gas barrier coating layer 15 serves to improve the gas barrier properties and protect the inorganic oxide layer 14. The gas barrier coating layer 15 is not particularly limited, and may include a hydroxyl-containing polymer compound, specifically, a heated dried product of a composition containing at least one of a hydroxyl-containing polymer compound and its hydrolyzate and at least one selected from metal alkoxides, silane coupling agents, and their hydrolyzates.

[0084] The gas barrier coating layer 15 can be formed, for example, using a composition (hereinafter referred to as a top coating agent) obtained by adding a hydroxyl-containing polymer compound and a metal alkoxide and / or a silane coupling agent to water or a water / alcohol mixture. The top coating agent can be prepared, for example, by directly mixing a solution of a hydroxyl-containing polymer compound as a water-soluble polymer dissolved in an aqueous (water or water / alcohol mixture) solvent with a metal alkoxide and / or a silane coupling agent; or by mixing with a metal alkoxide and / or a silane coupling agent that has been subjected to a hydrolysis treatment or the like in advance.

[0085] Examples of hydroxyl-containing polymer compounds include polyvinyl alcohol, ethylene-vinyl alcohol copolymers, polyvinyl pyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. Among them, polyvinyl alcohol (PVA) is preferably used in the topcoat agent of the gas barrier coating layer because it has particularly excellent gas barrier properties.

[0086] Examples of the metal alkoxide include compounds represented by the following general formula (I).

[0087] M(OR 1 ) m (R 2 ) n-m (I)

[0088] In the above general formula (I), R 1 and R 2 Each independently represents a monovalent organic group having 1 to 8 carbon atoms, preferably an alkyl group such as methyl or ethyl. M represents an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer from 1 to n. 1 or R 2 When there are multiple 1 Between or R 2 They can be the same or different.

[0089] Specific examples of the metal alkoxide include tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], etc. Tetraethoxysilane and triisopropoxyaluminum are preferred because they are relatively stable in an aqueous solvent after hydrolysis.

[0090] Examples of the silane coupling agent include compounds represented by the following general formula (II).

[0091] Si(OR 11 ) p (R 12 ) 3-p R 13 (II)

[0092] In the above general formula (II), R 11 represents an alkyl group such as methyl or ethyl, R 12 represents a monovalent organic group such as an alkyl group, an aralkyl group, an aryl group, an alkenyl group, an alkyl group substituted by an acryloyloxy group, or an alkyl group substituted by a methacryloyloxy group, and R 13 represents a monovalent organic functional group, and p represents an integer of 1 to 3. 11 or R 12 When there are multiple 11 Between or R 12 They may be the same or different. 13 The monovalent organic functional group shown in the figure includes glycidyloxy, epoxy, mercapto, hydroxyl, amino, alkyl substituted with a halogen atom, or a monovalent organic functional group containing an isocyanate group. The silane coupling agent may also be a polymer such as a dimer or trimer of the above silane coupling agents.

[0093] Specific examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane.

[0094] When the water-soluble polymer is PVA, the content of PVA in the mixed solution can be 20 to 50% by mass, or 25 to 40% by mass based on the total solid content of the mixed solution. When the content of PVA is 20% by mass or more, it is easy to form the gas barrier coating layer 15. When the content of PVA is 50% by mass or less, there is a tendency that the gas barrier properties of the laminate 100 become excellent.

[0095] The top coating agent may contain known additives such as an isocyanate compound, a dispersant, a stabilizer, a viscosity modifier, and a colorant as needed within a range that does not impair the gas barrier properties.

[0096] The top coating agent can be applied, for example, by dipping, roll coating, gravure coating, reverse gravure coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset printing, etc. The coating film formed by applying the top coating agent can be dried, for example, by hot air drying, hot roll drying, high frequency irradiation, infrared irradiation, UV irradiation, or a combination thereof.

[0097] The temperature during drying of the coating film may be, for example, 50 to 150° C., preferably 60 to 100° C. When the drying temperature is within the above range, cracking in the inorganic oxide layer or the gas barrier coating layer can be further suppressed, and excellent barrier properties can be exhibited.

[0098] The gas barrier coating layer can also be formed using a top coating agent containing a hydroxyl-containing polymer compound (eg, polyvinyl alcohol resin) and a silane compound. An acid catalyst, a base catalyst, a photopolymerization initiator, etc. can be added to the top coating agent as needed.

[0099] Examples of the silane compound include silane coupling agents, polysilazanes, and siloxanes. Specific examples include tetramethoxysilane, tetraethoxysilane, glycidoxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, and hexamethyldisilazane.

[0100] The thickness of the gas barrier coating layer is preferably 50 to 1000 nm, more preferably 100 to 500 nm. When the thickness of the gas barrier coating layer is 50 nm or more, more sufficient gas barrier properties tend to be obtained, and when it is 1000 nm or less, sufficient flexibility tends to be maintained.

[0101] (Sealing agent layer)

[0102] The sealant layer 30 is composed of a polyethylene resin, and is joined by hot melt bonding (heat sealing) when the laminate 100 is used to form a packaging material such as a packaging bag. From the viewpoint of heat sealability, the polyethylene resin constituting the sealant layer 30 is preferably a low-density polyethylene resin, a linear low-density polyethylene resin, and an ultra-low-density polyethylene resin. In addition, from the viewpoint of environmental load, it is preferred to use a biomass-derived polyethylene resin or a recycled polyethylene resin in the sealant layer 30. The sealant layer 30 can be composed of an unstretched polyethylene film. In the sealant layer 30, a copolymer of ethylene and other monomers can be used within the range that does not damage the characteristics of the laminate 100.

[0103] The thickness of the sealant layer 30 can be appropriately changed according to the weight of the content filled in the manufactured packaging material, etc. For example, when manufacturing a packaging bag filled with a content of 1 g or more and 200 g or less, the thickness of the sealant layer 30 is preferably 20 μm or more and 60 μm or less. By setting the thickness to 20 μm or more, leakage of the filled content due to damage of the sealant layer 30 can be prevented. By setting the thickness to 60 μm or less, the processing suitability of the laminate 100 can be improved.

[0104] As another example, when a self-supporting bag filled with a content of 50 g or more and 2000 g or less is produced, the thickness of the sealant layer 30 is preferably 50 μm or more and 200 μm or less. By setting the thickness to 50 μm or more, it is possible to prevent the filled content from leaking due to damage to the sealant layer 30. In addition, by setting the thickness to 200 μm or less, the processing suitability of the laminate 100 can be improved, and it is more preferably 150 μm.

[0105] (First and second adhesive layers)

[0106] The first adhesive layer 40 is a layer containing at least one adhesive, and is provided between the coextruded multilayer film 1 and the polyethylene film 20 to bond the two. The second adhesive layer 50 is a layer containing at least one adhesive, and is provided between the polyethylene film 20 and the sealant layer 30 to bond the two. Any adhesive such as a one-component curing type or a two-component curing type urethane adhesive can be used in the first adhesive layer 40 and the second adhesive layer 50. These adhesives may contain a layered inorganic compound for the purpose of further improving the barrier properties.

[0107] The first adhesive layer 40 or the second adhesive layer 50 may also be formed using an adhesive that exhibits gas barrier properties after curing. In particular, when an adhesive layer in contact with an inorganic oxide layer is formed using an adhesive that exhibits gas barrier properties, the reduction in gas barrier properties caused by cracks in the inorganic oxide layer can be further suppressed. Thus, the gas barrier performance of the laminate 100 can be further improved. As such gas barrier adhesives, epoxy adhesives, polyester-polyurethane adhesives, and the like can be cited. As specific examples, "Maxive" manufactured by Mitsubishi Gas Chemical Co., Ltd. and "Paslim" manufactured by DIC Corporation can be cited.

[0108] The thickness of the first adhesive layer 40 and the second adhesive layer 50 is preferably 0.5 μm or more and 6 μm or less, more preferably 0.8 μm or more and 5 μm or less, and further preferably 1.0 μm or more and 4.5 μm or less. By setting the thickness of the first adhesive layer 40 and the second adhesive layer 50 to be 0.5 μm or more, the adhesion of the first adhesive layer 40 and the second adhesive layer 50 can be improved. By setting the thickness of the first adhesive layer 40 and the second adhesive layer 50 to be 6 μm or less, the processing suitability of the laminate 100 can be improved.

[0109] The first adhesive layer 40 and the second adhesive layer 50 can be formed by various known methods such as direct gravure roll coating, gravure roll coating, contact coating, reverse roll coating, spraying, and transfer coating.

[0110] The laminate 100 includes polyethylene resin by the coextruded multilayer film 1, the polyethylene film 20, and the sealant layer 30, and the content ratio of the polyethylene resin in the laminate 100 becomes 90 mass % or more based on the total amount of the laminate 100. Therefore, the laminate 100 has high recyclability. When the coextruded multilayer film 1, the polyethylene film 20, and the sealant layer 30 are all formed only of polyethylene resin, the ratio (mass %) of the polyethylene resin in the laminate 100 can be calculated using the following formula (1).

[0111] (mass of the coextruded multilayer film 1 + mass of the polyethylene film 20 + mass of the sealant layer 30) / mass of the entire laminate 100 × 100 (1)

[0112] In the laminate 100, the difference between the heat-sealing start temperature of the surface layer 10 of the coextruded multilayer film 1 and the heat-sealing start temperature of the sealant layer 30 is preferably 40° C. or more from the viewpoint of ensuring good sealing properties, and more preferably 50° C. or more because the range of heat-sealing temperature conditions during bag making is widened, heat sealing at high temperatures becomes possible, and thus the bag making efficiency can be improved. The difference between the heat-sealing start temperature of the surface layer of the coextruded multilayer film and the heat-sealing start temperature of the sealant layer refers to a value measured by the method described in the examples described later.

[0113] When one laminate 100 is bent while the sealant layers 30 are facing each other, or two laminates 100 are overlapped while the sealant layers 30 are facing each other, and the filling part of the contents is left and the sealant layers 30 at the edge are joined by heat sealing, a packaging bag formed by the laminate 100 can be formed. By performing the above-mentioned joining while clamping the bent base film, a self-supporting bag can be formed. In addition, various packaging bags such as pillow bag packaging, four-side sealed bags, three-side sealed bags, and accordion bags can be made and used. In this way, the laminate 100 can be used in various packaging bags. The laminate 100 can be preferably used in packaging bags for purposes of boiling treatment (for example, boiling temperature: above 95°C).

[0114] <Second embodiment>

[0115] A laminated body according to the second embodiment will be described below. Aspects not described below are the same as those of the laminated body according to the first embodiment unless there is any mismatch. Figure 4 This is a schematic cross-sectional view of a laminated body according to a second embodiment of the present disclosure. Figure 4 The laminate 200 shown is different from the laminate 100 in that the polyethylene film 20 has a surface layer 20 a , an intermediate layer 20 b , and a back layer 20 c in this order.

[0116] The surface layer 20a preferably comprises a 0.926 g / cm 3 The polyethylene resin having a density of more than 100%, preferably includes at least one selected from medium-density polyethylene resin and high-density polyethylene resin. The back layer 20c preferably includes at least one selected from medium-density polyethylene resin and high-density polyethylene resin. The middle layer 20b preferably includes a high-density polyethylene resin. Thus, the processing stability and heat resistance when the inorganic oxide layer 14 is provided can be improved while having the surface smoothness of the polyethylene film 20.

[0117] The overall density of the polyethylene film 20 is preferably 0.942 g / cm 3 above.

[0118] The thickness of the intermediate layer 20 b is preferably 1 / 3 or more of the entire polyethylene film 20 from the viewpoint of heat resistance.

[0119] In the polyethylene film 20, the probe drop temperature of the middle layer 20b is preferably higher than the probe drop temperature of the surface layer 20a, and is higher than the probe drop temperature of the back layer 20c. As a result, the polyethylene film 20 has a tendency that the surface of the surface layer 20a is difficult to become rough, it is difficult to generate defects when the inorganic oxide layer 14 is formed, and excellent heat resistance can be achieved. As a result, the laminate 200 becomes difficult to wrinkle, has excellent processing stability, and is easier to maintain gas barrier properties even after heat sterilization.

[0120] The probe descent temperature is measured as follows. That is, an atomic force microscope equipped with a nanothermal microscope composed of a cantilever (probe) with a heating device is used, and the cantilever (probe) is brought into contact with the surface of a polyethylene film (sample) fixed on a sample stand. When a certain force (touch pressure) is applied to the cantilever (probe) in contact mode and a voltage is applied to heat it, the sample surface undergoes thermal expansion, and the cantilever (probe) rises. Furthermore, when the cantilever (probe) is heated, the sample surface softens, and a significant change in hardness is visible, and the cantilever (probe) descends and penetrates into the sample surface. The rapid displacement change at this time is detected. The point at which the voltage changes is the starting point of the probe descent, and the probe descent temperature is obtained by converting the voltage into a temperature.

[0121] The above describes the laminates of the first and second embodiments, but the laminates of the present disclosure are not limited to the above embodiments. For example, the laminate may include a coextruded multilayer film 2 instead of the coextruded multilayer film 1. The laminate may further include a printed layer. In addition, the laminate may not include one or more of the polyethylene film, the inorganic oxide layer, and the gas barrier coating layer. When the laminate does not include a polyethylene film, the first adhesive layer is unnecessary, and the inorganic oxide layer may be provided on the coextruded multilayer film. In addition, the gas barrier layer may be provided between the coextruded multilayer film and the polyethylene film. In this case, the laminate may be Figure 5 As shown.

[0122] Figure 5 The laminate 300 shown has an inorganic oxide layer 14 and a gas barrier coating layer 15 between the coextruded multilayer film 1 and the polyethylene film 20. As a result, the obtained packaging bag can suppress the influence of the contents on the gas barrier layer and has a tendency to improve the gas barrier property. The polyethylene film 20 is arranged in such a way that the surface layer 20a is located on the inorganic oxide layer 14 side and the back layer 20c is located on the second adhesive layer 50 side.

[0123] [Coextruded multilayer film of the second aspect]

[0124] The following describes the coextruded multi-layer film of the second aspect of the present disclosure in terms of differences from the coextruded multi-layer film of the first aspect.

[0125] Figure 6 It is a schematic cross-sectional view of a coextruded multilayer film according to one embodiment of the present disclosure. Figure 6 The coextruded multilayer film 3 shown has a surface layer (first layer) 10, an intermediate layer (second layer) 12, and a back layer (third layer) 11. The coextruded multilayer film 3 is manufactured by a coextrusion method. The intermediate layer 12 contains a polyethylene resin. The thickness of the surface layer 10 is greater than 0.3 μm and less than 6 μm. The following describes each layer.

[0126] (surface layer)

[0127] The skin layer 10 contains a resin having a higher melting point than the polyethylene resin contained in the intermediate layer 12. The structure of the skin layer 10 other than this may be the same as that of the skin layer 10 of the coextruded multilayer film of the first aspect.

[0128] (Middle layer)

[0129] The intermediate layer 12 may have the same structure as the back layer 11 of the coextruded multilayer film of the first aspect. The intermediate layer 12 may be a single layer or a plurality of layers.

[0130] (Back layer)

[0131] The back layer 11 contains a resin having a higher melting point than the polyethylene resin contained in the middle layer 12. The back layer 11 plays a role in reducing the difference in thermal properties between the surface layer 10 side and the back layer 11 side in the coextruded multilayer film 3 to suppress curling. In addition, the back layer 11 plays a role in providing sufficient adhesion when the coextruded multilayer film 3 is stretched and pasted with other layers.

[0132] Examples of the resin having a higher melting point than the polyethylene resin include polypropylene resin, polyester resin, polyamide resin, ethylene-vinyl alcohol copolymer, polyvinyl alcohol resin, polyvinylidene chloride resin and polystyrene resin. These resins may be used alone or in combination of two or more.

[0133] The melting point of the resin having a higher melting point than the polyethylene resin may be 160° C. or higher, 180° C. or higher, or 200° C. or higher from the viewpoint that the coextruded multilayer film 3 has more excellent heat sealability.

[0134] The content of the resin having a melting point higher than that of the polyethylene resin may be 10 mass % or more, 30 mass % or more, 50 mass % or more, 70 mass % or more, 90 mass % or more, 95 mass % or more, or 100 mass % based on the total amount of the back layer 11 .

[0135] When the coextruded multilayer film 3 is produced by the T-die method, the melt flow rate (MFR) of the resin having a melting point higher than that of the polyethylene resin is preferably 3 g / 10 minutes or more and 20 g / 10 minutes or less. By making the MFR to be 3 g / 10 minutes or more, the processing suitability of the coextruded multilayer film 3 can be improved. In addition, by making the MFR to be 20 g / 10 minutes or less, the coextruded multilayer film 3 produced can be prevented from breaking.

[0136] When the coextruded multilayer film 3 is produced by the inflation method, the MFR of the resin having a melting point higher than that of the polyethylene resin is preferably 0.1 g / 10 minutes or more and 5 g / 10 minutes or less. By making the MFR 0.1 g / 10 minutes or more, the processing suitability of the coextruded multilayer film 3 can be improved. In addition, by making the MFR 5 g / 10 minutes or less, the film forming property can be improved.

[0137] The back layer 11 may further include a polyethylene resin. When the back layer 11 includes a polyethylene resin, when the back layer 11 and the layer formed by the polyethylene resin are attached, even if no adhesive resin is used between the layers, a close adhesion strength that is difficult to peel between the layers can be given. The content ratio of the polyethylene resin can be 10% by mass or more, 30% by mass or more, 50% by mass or more, 70% by mass or more, or 90% by mass or more based on the total amount of the back layer 11.

[0138] The thickness of the back layer 11 may be 0.3 μm or more, 0.5 μm or more, or 1 μm or more, and may be 6 μm or less, 5 μm or less, or 3 μm or less.

[0139] In the coextruded multilayer film 3, by making the thickness of the surface layer 10 and the back layer 11 the same, the occurrence of curling can be further suppressed.

[0140] [Laminate of the Second Aspect]

[0141] Hereinafter, regarding the laminated body according to the second aspect of the present disclosure, aspects different from the laminated body according to the first aspect will be described.

[0142] <First embodiment>

[0143] Figure 7 It is a schematic cross-sectional view of a laminated body according to the first embodiment of the present disclosure. Figure 7 The laminate 400 shown includes a coextruded multilayer film 3, a first adhesive layer 40, a polyethylene film 20, a second adhesive layer 50, and a sealant layer 30. The laminate 400 includes an inorganic oxide layer 14 and a gas barrier coating layer 15 between the polyethylene film 20 and the sealant layer 30 as gas barrier layers.

[0144] The inorganic oxide layer, gas barrier coating layer, polyethylene film, sealant layer, first adhesive layer and second adhesive layer can respectively have the same structure as the inorganic oxide layer, gas barrier coating layer, polyethylene film, sealant layer, first adhesive layer and second adhesive layer of the stack of the first embodiment of the above-mentioned first aspect.

[0145] <Second embodiment>

[0146] A laminated body according to a second embodiment of the second aspect will be described below. Aspects not described below are the same as those of the laminated body according to the first embodiment of the second aspect unless there is any mismatch. Figure 8 This is a schematic cross-sectional view of a laminated body according to a second embodiment of the present disclosure. Figure 8 The laminate 500 shown is different from the laminate 400 in that the polyethylene film 20 has a surface layer 20 a , an intermediate layer 20 b , and a back layer 20 c in this order.

[0147] The polyethylene film 20 may have the same configuration as that of the polypropylene film of the laminate according to the second embodiment of the first aspect.

[0148] The first and second embodiments of the second aspect of the laminate are described above, but the laminate of the present disclosure is not limited to the above embodiments. For example, the laminate may further include a printing layer. In addition, the laminate may not include one or more of the polyethylene film, the inorganic oxide layer, and the gas barrier coating layer. When the laminate does not include a polyethylene film, the first adhesive layer is not required, and the inorganic oxide layer may be provided on the coextruded multilayer film. In addition, the gas barrier layer may be provided between the coextruded multilayer film and the polyethylene film. In this case, the laminate may be Fig. 9 As shown.

[0149] Fig. 9 The laminate 600 shown has an inorganic oxide layer 14 and a gas barrier coating layer 15 between the coextruded multilayer film 3 and the polyethylene film 20. As a result, the obtained packaging bag can suppress the influence of the contents on the gas barrier layer and has a tendency to improve the gas barrier property. The polyethylene film 20 is arranged in such a way that the surface layer 20a is located on the inorganic oxide layer 14 side and the back layer 20c is located on the second adhesive layer 50 side.

[0150] Example

[0151] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to these examples.

[0152] {First Study}

[0153] [Material]

[0154] (Preparation of Adhesive)

[0155] Adhesive A, which is a urethane adhesive, was prepared by mixing 11 parts by mass of TAKELAC A525 manufactured by Mitsui Chemicals, Inc. and 84 parts by mass of ethyl acetate with 100 parts by mass of TAKELAC A525 manufactured by Mitsui Chemicals, Inc.

[0156] (Preparation of Primer Layer Forming Composition)

[0157] Acrylic polyol and toluene diisocyanate were mixed so that the number of OH groups of acrylic polyol and the number of NCO groups of toluene diisocyanate were equal, and diluted with ethyl acetate so that the total solid content (the total amount of acrylic polyol and toluene diisocyanate) was 5% by mass. β-(3,4-epoxycyclohexyl)trimethoxysilane was further added to the diluted mixed solution so that it was 5 parts by mass relative to 100 parts by mass of the total amount of acrylic polyol and toluene diisocyanate, and these were mixed to prepare a primer layer-forming composition (anchor coating agent).

[0158] (Preparation of top coating agent)

[0159] The following liquid A, liquid B, and liquid C were mixed at a mass ratio of 70 / 20 / 10 to prepare a top coating agent.

[0160] Liquid A: A hydrolyzed solution having a solid content of 5% by mass (based on SiO2) was obtained by adding 72.1 g of 0.1N hydrochloric acid to 17.9 g of tetraethoxysilane (Si(OC2H5)4) and 10 g of methanol and stirring for 30 minutes to hydrolyze.

[0161] Solution B: 5 mass % water / methanol solution of polyvinyl alcohol (mass ratio of water:methanol is 95:5)

[0162] Solution C: A hydrolysis solution prepared by diluting 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate with a water / isopropyl alcohol mixture (water:isopropyl alcohol mass ratio is 1:1) to a solid content of 5% by mass.

[0163] [Sealing agent layer]

[0164] As materials for the sealant layer, "TUX MC-S", "TUX VCS", "TUX HC" and "TUX TC-S" (all of which are products manufactured by Mitsui Chemicals Tohcello Co., Ltd., polyethylene films) were prepared.

[0165] [Resins constituting multilayer films and polyethylene films]

[0166] As resins constituting the multilayer film and the polyethylene film, the following materials were prepared.

[0167] PP(A): Polypropylene resin (melting point 160°C, density 0.9g / cm 3 、MFR: 0.8g / 10min (190℃, 2.16kg) 、Made by Japan Polypropylene, EG8B (product brand)

[0168] PA(A): Polyamide resin (melting point 220°C, density 1.15 g / cm3 , Relative viscosity 3.04, Ube Industries, Polyamide 6 1020 (product brand)

[0169] PBT(A): Polybutylene terephthalate resin (melting point 215°C, density 1.35 g / cm 3 , MFR: 4 g / 10 min (190°C, 2.16 kg)), Toray, 1400S (product brand)

[0170] EVOH (A): Ethylene-vinyl alcohol copolymer (melting point 183°C, density 1.19 g / cm 3 , MFR: 1.6 g / 10 min (190°C, 2.16 kg)), Kuraray, F171B (product brand)

[0171] PE(A): Polyethylene resin (melting point 133°C, density 0.958 g / cm 3 , MFR: 1g / 10min (190°C, 2.16kg)), Primepolymer, 3600F (product brand)

[0172] PE(B): Polyethylene resin (melting point 130°C, density 0.95g / cm 3 , MFR: 1.1 g / 10 min (190°C, 2.16 kg)), Primepolymer, 3300F (product brand)

[0173] PE(C): Polyethylene resin (melting point 133°C, density 0.963g / cm 3 , MFR: 1.35 g / 10 min (190°C, 2.16 kg)), Asahi Kasei, B161 (product brand)

[0174] PE(D): Polyethylene resin (melting point 129°C, density 0.941 g / cm 3 , MFR: 1.3 g / 10 min (190°C, 2.16 kg)), Dow Chemical, 5538G (product brand)

[0175] PE(E): Polyethylene resin (melting point 134°C, density 0.962g / cm 3 , MFR: 0.85 g / 10 min (190°C, 2.16 kg)), Dow Chemical, 5960G1 (product brand)

[0176] PE(F): Polyethylene resin (melting point 124°C, density 0.92g / cm 3, MFR: 0.85 g / 10 min (190°C, 2.16 kg)), Dow Chemical, 5100G (product brand)

[0177] Adhesive resin (A): Adhesive resin (melting point 119°C, density 0.9 g / cm 3 , MFR: 1 g / 10 min (190°C, 2.16 kg)), Dow Chemical, M512 (product brand)

[0178] [Production of co-extruded multilayer films]

[0179] <Examples A1-1 to A1-14, Examples A2-1 to A2-11, and Comparative Examples A1-1 to A1-3>

[0180] A coextruded multilayer film is produced by a coextrusion air cooling inflation method. Specifically, first, extruders 1 to 5 are prepared. The materials shown in Tables 1 to 5, 7 and 9 are filled in each extruder, respectively. When two materials are mixed and used, the material names and their mixing ratios (mass ratios) are shown in the table. The filled materials are melt-kneaded (temperature: 190 to 230° C.). The molten materials are extruded from each extruder and laminated, and air-cooled to produce a coextruded multilayer film. The materials of each extruder are extruded in such a way that the thickness reaches the values ​​shown in Tables 1 to 5, 7 and 9.

[0181] [Production of polyethylene film]

[0182] <Examples A2-1 to A2-11>

[0183] A co-extruded multilayer film is produced by a co-extrusion air cooling inflation method. Specifically, first, extruders 1 to 3 are prepared. The materials shown in Tables 5 and 7 are filled in each extruder, respectively. The filled materials are melt-kneaded (temperature: 190 to 230° C.). The molten materials are extruded from each extruder and laminated, and air-cooled to produce a polyethylene film. The surface of the obtained polyethylene film is subjected to a corona treatment. The polyethylene film of Example A2-7 is stretched in the MD direction at a ratio of 2 to 5 times.

[0184] [Production of Laminated Body]

[0185] <Examples A1-1 to A1-14 and Comparative Examples A1-1 to A1-3>

[0186] The back layer surface of the coextruded multilayer film and the sealant layer were adhered to each other by dry lamination using adhesive A, and then aged (temperature: 40°C, duration: 4 days) to obtain a laminate. The thickness of the adhesive layer was 3 μm. The sealant layer used the materials shown in Tables 1 to 4 and 9.

[0187] <Examples A2-1 to A2-11>

[0188] (Formation of Primer Layer)

[0189] The undercoat layer-forming composition was applied to the corona-treated surface layer of the polyethylene film by gravure coating to form a coating film, and the coating film was dried to form an undercoat layer having a thickness of 0.1 μm.

[0190] (Formation of Inorganic Oxide Layer)

[0191] On the above-mentioned undercoat layer, a transparent inorganic oxide layer made of silicon oxide or aluminum oxide is formed to a thickness of 30 nm by a vacuum evaporation device using an electron beam heating method.

[0192] (Formation of Gas Barrier Coating Layer)

[0193] On the inorganic oxide layer, a top coating agent was applied by gravure coating to form a coating film, and the coating film was dried to form a gas barrier coating layer having a thickness of 0.3 μm and having a gas barrier function.

[0194] The surface of the gas barrier coating layer side of the polyethylene film was adhered to the sealant layer by dry lamination using adhesive A to obtain a first laminate. The back layer side surface of the coextruded multilayer film of the first laminate was adhered to the back layer side surface of the polyethylene film by dry lamination using adhesive A to obtain a second laminate. The second laminate was aged (temperature: 40°C, duration: 4 days) to obtain a laminate. The thickness of each adhesive layer was 3 μm. The sealant layer used the materials shown in Tables 5 and 7.

[0195] [Evaluation of Laminated Body]

[0196] The laminated body obtained in each example was evaluated as follows. The results are shown in Tables 1 to 4, 6, 8, and 9.

[0197] <Recyclability>

[0198] The content ratio (mass %) of the polyethylene resin in the laminate of each example was calculated. The content ratio of the polyethylene resin was evaluated according to the following criteria.

[0199] (standard)

[0200] A: The content of the polyethylene resin is 90% by mass or more.

[0201] C: The content of the polyethylene resin is less than 90% by mass.

[0202] <Heat sealability>

[0203] The laminate is cut into 10 cm squares as evaluation samples. The sample is observed from the sealant layer side and folded, and heat-sealed using a heat seal tester (pressure: 0.2 MPa, heating time: 1 second). Afterwards, visually confirm whether the laminate is melt-bonded on the heat seal rod. Also confirm whether there is melt-bonding of the sealant layer of the sample. This operation is performed at various heat seal temperatures, and the highest temperature (maximum temperature) and the lowest temperature (minimum temperature) at which the sealant layers of the sample are melt-bonded and the melt-bonding of the laminate on the heat seal rod is not confirmed are measured. Calculate the difference between the highest temperature and the lowest temperature (heat seal temperature condition amplitude) and evaluate according to the following standards. In addition, visually confirm the appearance of the heat-sealed portion of the sample obtained by heat sealing at a heat seal temperature of 140°C, and evaluate according to the following standards.

[0204] (Evaluation criteria for heat sealing temperature range)

[0205] A: Heat sealing temperature range is above 20℃

[0206] B: The heat sealing temperature range is 0°C or higher and less than 20°C.

[0207] (Appearance Standard)

[0208] A: No wrinkles were observed in the heat-sealed portion.

[0209] B: Wrinkles were observed in the heat-sealed portion to a degree that allows the portion to be used.

[0210] C: Wrinkles were observed in the heat-sealed portion to such an extent that the product could not be used.

[0211] <Heat sealing start temperature>

[0212] The surface layers of the coextruded multilayer film in the laminate obtained in each example are facing each other, and heat sealing is performed using a heat sealer manufactured by Tester Industry Co., Ltd. under the conditions of a sealing pressure of 0.2MPa, a sealing time of 1 second, and a sealing width of 5mm. The sealing temperature is adjusted at 10°C between 130°C and 240°C. Afterwards, the films heat-sealed at each temperature are cut into 15mm wide × 80mm, and a tensile testing machine manufactured by Shimadzu Corporation is used to perform T-peeling at a tensile speed of 300mm / min to measure the heat seal strength of the heat-sealed part. The temperature at which the heat seal strength reaches 2N / 15mm or more is used as the heat seal start temperature of the surface layer of the multilayer film. For the sealant layer of the laminate obtained in each example, the heat seal start temperature is also measured in the same manner as the surface layer of the multilayer film. In addition, the difference between the start temperature of the surface layer of the multilayer film and the start temperature of the sealant layer is calculated.

[0213] <Suitability for barrier processing>

[0214] The appearance and curling state of the laminate obtained in each example were visually observed and evaluated according to the following criteria.

[0215] (standard)

[0216] A: No wrinkles were observed in the appearance of the gas barrier film.

[0217] B: Slight wrinkles were observed in the appearance of the gas barrier film.

[0218] C: Many wrinkles were observed in the appearance of the gas barrier film.

[0219] <Gas barrier properties>

[0220] (No boiling)

[0221] The oxygen permeability of the laminate was measured at a temperature of 30°C and a relative humidity of 70% according to JIS K 7126-2 (unit: cc / m 2 ·day·atm) and evaluated according to the following criteria.

[0222] (standard)

[0223] A: Oxygen permeability is less than 2cc / m 2 ·day·atm

[0224] B: Oxygen permeability is 2cc / m 2 ·day·atm or more and less than 10cc / m 2 ·day·atm

[0225] C: Oxygen permeability is 10cc / m 2 ·day·atm or more

[0226] (with boiling)

[0227] Cut the laminate into a size of 15cm×10cm, overlap the two cut packaging films so that the sealant layers face each other, and pulse seal the three sides into a bag. Put 200ml of tap water as the content in the bag, pulse seal the remaining side to make a bag (packaging bag) with four sides sealed. Boil the obtained bag at 95°C for 30 minutes using a boiling treatment device. After boiling, open the bag, discard the tap water in the bag, and dry it thoroughly. Cut the laminate out of the bag, and measure the oxygen permeability using the same method as the gas barrier evaluation without boiling. Evaluate the oxygen permeability according to the following standards.

[0228] (standard)

[0229] A: Oxygen permeability is less than 2cc / m 2 ·day·atm

[0230] B: Oxygen permeability is 2cc / m 2 ·day·atm or more and less than 10cc / m 2 ·day·atm

[0231] C: Oxygen permeability is 10cc / m 2 ·day·atm or more

[0232] D: The sealant layers were fused together and the oxygen permeability could not be measured.

[0233] <Molecular orientation>

[0234] The polyethylene film was rotated in a microwave polarized electric field using a microwave molecular orientation meter (manufactured by Oji Scientific Instruments Co., Ltd., trade name MOA-5012A) to measure the molecular orientation degree of molecular chains in the polyethylene film plane.

[0235] <Probe drop temperature>

[0236] As the atomic force microscope, MPF-3D-SA (trade name) manufactured by Oxford Instruments was used, and as the nanothermal microscope equipped therein, Ztherm (trade name) manufactured by Oxford Instruments was used. As the cantilever (probe), AN2-200 (trade name) manufactured by Anaxis Instruments was used.

[0237] The polyethylene film of each example was cut at an arbitrary position and a cross-sectional sample was prepared using a cryo-microtome at -140° C. The conditions for preparing the cross-sectional sample were a cutting thickness of 100 nm, a cutting speed of 1 mm / s, and a diamond knife.

[0238] After measuring the shape of the sample with a 10μm field of view in AC mode, the cantilever (probe) and the sample are separated by 5 to 10μm in the Z direction. In this state, the Detrend correction function of the device is performed in contact mode under the conditions of a maximum applied voltage of 6V and a heating rate of 0.5V / s to correct the change in the bending amount (Deflection) of the cantilever (probe) caused by voltage application. After that, the cantilever is contacted to the sample in contact mode in such a way that the change in Deflection before and after the cantilever contacts the sample becomes 0.2V. While keeping the Deflection at a constant value, a voltage is applied to the cantilever and the sample is heated under the conditions of a maximum applied voltage of 6V and a heating rate of 0.5V / s. The change in Z displacement at this time is recorded, and the measurement is stopped when the Z displacement changes from rising to falling and the distance from the change point drops by 50nm. When the Z displacement reaches the maximum applied voltage without dropping by 50nm from the change point, the maximum applied voltage during the Detrend correction and measurement is increased by 0.5V and the measurement is performed again. The applied voltage at which the recorded Z displacement reaches the maximum is converted into a temperature and is taken as the probe descent temperature. This measurement is performed at 10 points within a 10 μm field of view, and the average value is used. The ranking of the probe descent temperatures of the surface layer, the middle layer, and the back layer is shown in the table.

[0239] In order to convert the applied voltage into temperature, polycaprolactone (melting point of 60°C), low-density polyethylene resin (melting point of 112°C), polypropylene resin (melting point of 166°C), and polyethylene terephthalate resin (melting point of 255°C) were used as calibration samples for measurement, and a standard curve of applied voltage and temperature was prepared. Here, the melting point is the melting peak temperature measured by a differential scanning calorimeter (DSC) under the condition of a heating rate of 5°C / min. The measurement method is the same as the measurement of the sample, but the maximum applied voltage during Detrend correction and measurement is set to 3.5V for polycaprolactone, 5.5V for low-density polyethylene, 6.5V for polypropylene, and 7.8V for polyethylene terephthalate. The relationship between the melting point and the applied voltage at which the Z displacement reaches the maximum when measuring each calibration sample is approximated by the least squares method using a cubic function, and a standard curve is prepared to convert the applied voltage when measuring the sample into temperature.

[0240] <Adhesion strength>

[0241] A 15 mm wide strip test piece was cut out from the laminate obtained in each embodiment and comparative example. The coextruded multilayer film and the sealant layer were peeled off from the end of the test piece using a TENSILON universal testing machine RTC-1250 manufactured by Orientec, and the interlayer adhesion strength was measured. The measurement was performed by T-peeling under normal conditions (temperature: 23°C, humidity: 50% RH) at a peeling speed of 300 mm / min. In addition, the peeling was performed while wetting the peeling interface with water (temperature: 23°C, humidity: 50% RH) at a peeling speed of 300 mm / min. The results were evaluated according to the following standards.

[0242] (Normal Standard)

[0243] A: The sealing strength is 2N / 15mm or more

[0244] B: Sealing strength is less than 2N / 15mm

[0245] (Standard for wet conditions)

[0246] A: The sealing strength is 2N / 15mm or more

[0247] B: Sealing strength is less than 2N / 15mm

[0248]

[0249]

[0250]

[0251]

[0252]

[0253]

[0254]

[0255]

[0256]

[0257] {Second Study}

[0258] [Material]

[0259] Prepare the same materials as in the first study.

[0260] [Production of co-extruded multilayer films]

[0261] <Examples B1-1 to B1-28, Examples B2-1 to B2-21, and Comparative Examples B1 to B4>

[0262] A coextruded multilayer film is produced by a coextrusion air cooling inflation method. Specifically, first, extruders 1 to 5 are prepared. The materials shown in Tables 10 to 15, 17, 19, 21 and 23 are filled in each extruder, respectively. When two materials are mixed and used, the material names and their mixing ratios (mass ratios) are shown in the table. The filled materials are melt-kneaded (temperature: 190 to 230°C). The molten materials are extruded from each extruder and stacked, and air-cooled to produce a coextruded multilayer film. The material of each extruder is extruded in such a way that the thickness reaches the values ​​shown in Tables 10 to 15, 17, 19, 21 and 23. As shown in the table, a portion of the coextruded multilayer film was stretched at a ratio of 2 to 5 times in the MD direction.

[0263] [Production of polyethylene film]

[0264] <Examples B2-1 to B2-21>

[0265] A co-extruded multilayer film is produced by a co-extrusion air cooling inflation method. Specifically, first prepare extruders 1 to 3. Fill each extruder with the materials shown in Tables 15, 17, 19 and 21. Melt and knead the filled materials (temperature: 190 to 230°C). The molten materials are extruded from each extruder and laminated, and air-cooled to produce a polyethylene film. The surface of the obtained polyethylene film is subjected to a corona treatment. The polyethylene films of Examples B2-7 and B2-18 are stretched in the MD direction at a ratio of 2 to 5 times.

[0266] [Production of Laminated Body]

[0267] <Examples B1-1 to 1-28 and Comparative Examples B1 to B4>

[0268] The back layer side surface of the coextruded multilayer film and the sealant layer were adhered to each other by dry lamination using adhesive A and aged (temperature: 40°C, duration: 4 days) to obtain a laminate. The thickness of the adhesive layer was 3 μm. The sealant layer used the materials shown in Tables 10 to 14 and 23.

[0269] <Examples B2-1 to B2-21>

[0270] A laminate was obtained in the same manner as in Example A2-1 of the first study except that the coextruded multilayer films of Examples B2-1 to B2-21 were used and the sealant layer shown in the table was used.

[0271] [Evaluation of Laminated Body]

[0272] The laminate obtained in each example was evaluated as follows. The results are shown in the table. Evaluation of recyclability, heat sealability, heat seal start temperature, barrier processing suitability, gas barrier properties, molecular orientation, and probe drop temperature were performed in the same manner as in the first study.

[0273] <Curly Review>

[0274] The coextruded multilayer film was cut into pieces with a size of 200 mm in the TD direction and 200 mm in the MD direction, and placed on a horizontal surface. The curling was observed from the horizontal surface to the four corners of the coextruded multilayer film. The degree of curling was evaluated according to the following criteria.

[0275] (standard)

[0276] A: No curling is observed in the coextruded multilayer film

[0277] B: Slightly visible curl in the coextruded multilayer film

[0278] C: Coextruded multilayer film curling

[0279] <Adhesion strength>

[0280] (Sealing strength 1)

[0281] A 15 mm wide strip test piece was cut out from the laminate obtained in each embodiment and comparative example. The coextruded multilayer film and the sealant layer were peeled off from the end of the test piece using a TENSILON universal testing machine RTC-1250 manufactured by Orientec, and the interlayer adhesion strength was measured. The measurement was performed by T-peeling under normal conditions (temperature: 23°C, humidity: 50% RH) at a peeling speed of 300 mm / min. In addition, the peeling was performed while wetting the peeling interface with water (temperature: 23°C, humidity: 50% RH) at a peeling speed of 300 mm / min.

[0282] (Sealing strength 2)

[0283] A test piece was cut out in the same manner as in Adhesion Strength 1. The coextruded multilayer film and the polyethylene film were peeled off under the same conditions as in Adhesion Strength 1 to measure the interlayer adhesion strength. In addition, the adhesion strength was measured in the same manner under the wet condition.

[0284] (Sealing strength 3)

[0285] The test piece was cut out in the same manner as in Adhesion Strength 1. The polyethylene film and the heat seal layer were peeled off under the same conditions as in Adhesion Strength 1 to measure the interlayer adhesion strength. In addition, the adhesion strength was measured in the same manner under the wet condition. The results were evaluated according to the following criteria.

[0286] (Normal Standard)

[0287] A: 2N / 15mm or more

[0288] B: less than 2N / 15mm

[0289] (Standard for wet conditions)

[0290] A: 2N / 15mm or more

[0291] B: less than 2N / 15mm

[0292]

[0293]

[0294]

[0295]

[0296]

[0297]

[0298]

[0299]

[0300]

[0301]

[0302]

[0303]

[0304]

[0305]

[0306] The gist of the present disclosure lies in the following [1] to

[10] .

[0307] [1] A coextruded multilayer film comprising a first layer and a second layer, wherein the second layer comprises a polyethylene resin,

[0308] The first layer comprises a resin having a higher melting point than the polyethylene resin,

[0309] The thickness of the first layer is 0.3 μm or more and 6 μm or less.

[0310] [2] The coextruded multilayer film according to [1], wherein

[0311] further having a third layer on a side of the second layer opposite to the first layer,

[0312] The third layer includes a resin having a higher melting point than the polyethylene resin.

[0313] [3] A laminate comprising:

[0314] The coextruded multilayer film according to [1] or [2];

[0315] a first adhesive layer disposed on one side of the second layer of the coextruded multilayer film; and

[0316] Sealant layer,

[0317] wherein the sealant layer comprises polyethylene resin,

[0318] The content of the polyethylene resin in the laminate is 90% by mass or more based on the total amount of the laminate.

[0319] [4] The laminate according to [3], wherein

[0320] The difference between the heat-seal starting temperature of the surface layer of the coextruded multilayer film and the heat-seal starting temperature of the sealant layer is 40° C. or more.

[0321] [5] The laminate according to [3] or [4], wherein

[0322] A polyethylene film and a second adhesive layer are further provided between the first adhesive layer and the sealant layer from the first adhesive layer side.

[0323] [6] The laminate according to [5], wherein

[0324] The absolute value of the molecular orientation degree of the polyethylene film is less than 1.07.

[0325] [7] The laminate according to [5] or [6], wherein

[0326] The polyethylene film has a surface layer, a middle layer, and a back layer in sequence.

[0327] In the polyethylene film, the probe drop temperature of the middle layer is higher than the probe drop temperature of the surface layer and is higher than the probe drop temperature of the back layer.

[0328] The surface layer of the polyethylene film comprises a polyethylene film having a 3 Polyethylene resin with a density above .

[0329] [8] The laminate according to any one of [4] to [7], wherein

[0330] A gas barrier layer is further provided between the coextruded multilayer film and the polyethylene film.

[0331] [9] The laminate according to any one of [5] to [7], wherein

[0332] A gas barrier layer is further provided between the polyethylene film and the sealant layer.

[0333]

[10] A packaging bag formed using the laminate according to any one of [3] to [9].

[0334] Explanation of symbols

[0335] 1, 2, 3 coextruded multilayer film, 20 polyethylene film, 30 sealant layer, 40, 50 adhesive layer, 100, 200, 300, 400, 500, 600 laminate.

Claims

1. A coextruded multilayer film comprising a first layer and a second layer, wherein: The second layer comprises a polyethylene resin, The first layer comprises a resin having a melting point higher than that of the polyethylene resin, The thickness of the first layer is greater than or equal to 0.3 μm and less than or equal to 6 μm.

2. The coextruded multilayer film according to claim 1, wherein The second layer further has a third layer on a side opposite to the first layer, The third layer includes a resin having a higher melting point than the polyethylene resin.

3. A laminate comprising: The coextruded multilayer film according to claim 1 or 2; a first adhesive layer disposed on one side of the second layer of the coextruded multilayer film; and Sealant layer, in, The sealant layer comprises a polyethylene resin, The content of the polyethylene resin in the laminate is 90% by mass or more based on the total amount of the laminate.

4. The laminate according to claim 3, wherein: The difference between the heat-seal start temperature of the surface layer of the coextruded multi-layer film and the heat-seal start temperature of the sealant layer is 40° C. or more.

5. The laminate according to claim 4, wherein A polyethylene film and a second adhesive layer are further provided between the first adhesive layer and the sealant layer from the first adhesive layer side.

6. The laminate according to claim 5, wherein The absolute value of the molecular orientation degree of the polyethylene film is less than 1.

07.

7. The laminate according to claim 5 or 6, wherein: The polyethylene film sequentially comprises a surface layer, a middle layer, and a back layer. In the polyethylene film, the probe drop temperature of the middle layer is higher than the probe drop temperature of the surface layer and is higher than the probe drop temperature of the back layer. The surface layer of the polyethylene film comprises a polyethylene film having a 3 Polyethylene resin with a density above .

8. The laminate according to any one of claims 5 to 7, wherein A gas barrier layer is further provided between the coextruded multi-layer film and the polyethylene film.

9. The laminate according to any one of claims 5 to 8, wherein A gas barrier layer is further provided between the polyethylene film and the sealant layer. 10 . A packaging bag formed using the laminate according to claim 3 .

Citation Information

Patent Citations

  • Laminate, packaging material, packaging bag and stand pouch

    JP2020055157A

  • Co-extruded multi-layer film and packaging material comprising this film

    JP2011025637A

  • Laminate, packaging material, packaging bag and stand pouch

    JP2020055158A

  • Laminate and packaging container

    JP2021160269A

  • Laminate and packaging container

    JP2021160270A